Medial Temporal Lobe Contributions to Intra-Item Associative Recognition Memory in the Aging Brain - Dalton, Marshall A.; Tu, Sicong; Hornberger, Michael; Hodges, John R.; Piguet, Olivier (Frontiers in Behavioral Neuroscience, 2014)
Ageing is associated with a decline in episodic memory function. This is accompanied by degradation of and functional changes in the medial temporal lobe (MTL) which subserves mnemonic processing. To date no study has investigated age related functional change in MTL substructures during specific episodic memory processes such as intra-item associative memory. The aim of this study was to characterise age related change in the neural correlates of intra-item associative memory processing. 16 young and 10 older subjects participated in a compound word intra-item associative memory task comprising a measure of associative recognition memory and a measure of recognition memory. There was no difference in performance between groups on the associative memory measure but each group recruited different MTL regions while performing the task. The young group recruited the left anterior hippocampus and posterior parahippocampal gyrus whereas the older participants recruited the hippocampus bilaterally. In contrast, recognition memory was significantly worse in the older subjects. The left anterior hippocampus was recruited in the young group during successful recognition memory whereas the older group recruited a more posterior region of the left hippocampus and showed a more bilateral activation of frontal brain regions than was observed in the young group. Our results suggest a reorganisation of the neural correlates of intra-item associative memory in the ageing brain.